Study on investigation of hot forging die wear analysis – An industrial case study. (2020) - Rajiev, R.; Sadagopan, P.; Shanmuga Prakash, R.
Abstract: Hot forging is a metal forming process mostly used in production industry. Hot forging dies are robustly affect by the stress increase during the hot forging process due to high temperature, plastic deformation of die and etc. In this study, wear analysis was carried out in AISI 316 stainless steel work piece material for pan head bolt component and EN19 work piece material for insert component and die were carried out in a local forging industry. The simulation of the forging process on the die and the work piece was carried out using commercially available software (DEFORM). The flow of the material in the die, die filling, contact pressure distribution, sliding velocities and temperature distribution of the die have been investigated. Experimental study has been conducted for various die pre heating temperature and wear on die has been studied. Finally intensity of wear in hot forging die cavity was calculated using the Finite Element simulation and then the total wear depth was established. By using simulation results the total wear depths were estimated at different locality of the hot forging die cavity and finally maximum significance of wear depth is attained.